Tika Tonu AD2020: Creating a Virtual Exhibition of Design Artwork in Response to The COVID-19 - Strickland, C; Rigby, H; Sanguanrachasab, J; Michie, K; Mpofu, N; Loh, C; Ferreira, N; Steagall, MM (School of Art and Design, Auckland University of Technology, 2020)
The year 2020 was marked by the economic and social challenges originating from the COVID-19 pandemic; measures were introduced to enforce social distancing in a battle against community transmission. Places like universities have been profoundly affected, forcing the adoption of new forms of delivery, where human contact was replaced with online classes on Blackboard. The industry was particularly affected, and many small offices and companies were forced to shut down, reducing the already-scarce professional work experience for students in the creative field. This industry component is part of the brief for Design students, and an essential part of the degree, offering opportunities for students to apply their learning in an authentic context.
This project emerged, firstly, from a scenario without abundant opportunities for students to complete their 60 hours of professional experience, a year-3 component of the Bachelor of Communication Design. Secondly, the project functions as a contextual response to the current context of uncertainty attached to the year of 2020.
In this sense, the main task for the research team was naturally decided to be the creation of a virtual exhibition, maintaining the tradition to have an annual graduation exhibition for the Communication Design cohort from AUT University. The goal of the project was to create an experience to satisfy the students’ need to exhibit their work in a world that has been transformed by restrictions due to the pandemic, added by the uncertainty produced by constant change in alert levels. The initial hypothesis is that the combination of a Human-Centred Design approach, Mixed Methods and Agile Prototyping could create the ideal environment for collaborative models that can be applied to complex problem-solving models in a rapidly changing world.
The paradigm selected by the researchers determines the methodology, and this project connects to post-positivist paradigm, where the inquiry is concerned with the subjectivity of reality and moves away from the purely objective stance adopted by the logical positivists. The great challenge was to organise a collaborative model for tasks which overlap multiple roles and actors to create a technology product. This process is followed by a thorough review of the contextual knowledge, providing insights about strategies that informed the development of the virtual exhibition, including case- studies of previous examples in the field. Agile sessions were conducted to explore Mind Mapping, Canvas and Prototyping (analogue and digital) techniques. Project planning was presented and implemented while usability tests and surveys were conducted to verify if the goals were achieved. The (exhibition name – blind review) exhibition facilitated the option for users to engage in a virtual tour of the design work, which may be experienced beyond the launch date. The researches process was documented in the form of an exegesis and an oral presentation in the international conference.
Keywords: Agile prototyping; Collaborative Design; Human Centred Design; Virtual Exhibition; Virtual Reality